Extracorporeal Treatment for Metformin Poisoning: Systematic Review and Recommendations From the Extracorporeal Treatments in Poisoning Workgroup. Issue 8 (August 2015) - Calello, Diane P.; Liu, Kathleen D.; Wiegand, Timothy J.; Roberts, Darren M.; Lavergne, Valéry; Gosselin, Sophie; Hoffman, Robert S.; Nolin, Thomas D.; Ghannoum, Marc
Abstract : Background: Metformin toxicity, a challenging clinical entity, is associated with a mortality of 30%. The role of extracorporeal treatments such as hemodialysis is poorly defined at present. Here, the Extracorporeal Treatments In Poisoning workgroup, comprising international experts representing diverse professions, presents its systematic review and clinical recommendations for extracorporeal treatment in metformin poisoning. Methods: A systematic literature search was performed, data extracted, findings summarized, and structured voting statements developed. A two-round modified Delphi method was used to achieve consensus on voting statements and RAND/UCLA Appropriateness Method to quantify disagreement. Anonymized votes and opinions were compiled and discussed. A second vote determined the final recommendations. Results: One hundred seventy-five articles were identified, including 63 deaths: one observational study, 160 case reports or series, 11 studies of descriptive cohorts, and three pharmacokinetic studies in end-stage renal disease, yielding a very low quality of evidence for all recommendations. The workgroup concluded that metformin is moderately dialyzable (level of evidence C) and made the following recommendations: extracorporeal treatment is recommended in severe metformin poisoning (1D). Indications for extracorporeal treatment include lactate concentration greater than 20 mmol/L (1D), pH less than or equal to 7.0 (1D), shock (1D), failure of standard supportive measures (1D), and decreased level of consciousness (2D). Extracorporeal treatment should be continued until the lactate concentration is less than 3 mmol/L (1D) and pH greater than 7.35 (1D), at which time close monitoring is warranted to determine the need for additional courses of extracorporeal treatment. Intermittent hemodialysis is preferred initially (1D), but continuous renal replacement therapies may be considered if hemodialysis is unavailable (2D). Repeat extracorporeal treatment sessions may use hemodialysis (1D) or continuous renal replacement therapy (1D). Conclusion: Metformin poisoning with lactic acidosis appears to be amenable to extracorporeal treatments. Despite clinical evidence comprised mostly of case reports and suboptimal toxicokinetic data, the workgroup recommended extracorporeal removal in the case of severe metformin poisoning. Abstract : Supplemental Digital Content is available in the text.